EPIDEMIOLOGY AND PREVENTION OF HIV INFECTION IN THE REPUBLIC OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Human Immunodeficiency Virus (HIV) is a chronic progressive anthroponotic disease with a contact transmission mechanism, which leads to specific damage to the immune system and the development of severe immunodeficiency. Due to its socio-medical and demographic significance, HIV infection is one of the most pressing problems of modern healthcare.Every year around the world, 2.5 million people are infected with HIV.According to the United Nations Program on HIV / AIDS Infection (UNAIDS), there are currently 38 million people living with HIV world-wide.Currently, HIV infection in Uzbekistan is detected among various groups of the population. In 2017, 4025 HIV-infected people were registered, and in 2018, there were 4060 people. In 2019, the incidence rate was 3983 people, and in 2019, the incidence rate decreased slightly.